PROBLEMATIKA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI TINGKAT SEKOLAH DASAR: STUDI KASUS SDN KEBONSARI KULON 3 KOTA PROBOLINGGO TAHUN AJARAN 2020-2021 - Abd. Komar; Nining Winarsih (UNZAH Genggong, 2020)
Social studies is one of the compulsory subjects in elementary schools. This subject contains lessons related to social life. With the existence of social studies lessons in elementary schools, it is hoped that students will have knowledge of the basic concepts of social science, sensitivity to social problems in their environment, and the role of humans as social beings. The research method used in this research is mixed methods, in which this research is a combination of two approaches, namely qualitative and quantitative. Data collection techniques in this study using observation, interview and documentation techniques. The subjects used in this study were teachers and students of Kebonsari Kulon 3 Elementary School, Probolinggo City, 2020-2021 academic year. Therefore, this research is expected to be able to be useful for the social sciences, especially because IPS or Social Studies has a noble task and becomes an important foundation for the intellectual, emotional, cultural and social development of students, namely being able to develop ways of thinking, behaving and behaving responsibly. as individuals, citizens of society, citizens, and citizens of the world. Keywords: Social Studies Learning, Problems, Learning Methods